Rare association - type I caudal regression syndrome associated with congenital spinal dermal sinus tract: a multimodality evaluation - Chandra, Shivani; Bansal, Lukshay; Prasad, Akhilandeswari (International Journal of Contemporary Pediatrics, 2024)
Caudal regression syndrome (CRS) and congenital spinal dermal sinus tract (CSDST) are two complex closed spinal dysraphism without subcutaneous mass. Embryo-pathogenesis behind CRS is deemed to be a fault during gastrulation, however CSDST is a result of defective focal disjunction during primary neurulation. While many associated congenital anomalies have been described with both of these entities, only a few literatures have ever described CRS and CSDST in unison. We present a case with both type 1 CRS with an intramedullary syringohydromyelia and a congenital spinal dermal sinus tract, with their multimodality imaging findings. Prompt identification and accurate diagnosis of CRS is cardinal for initiation of early and appropriate management, before the herald of dreadful complications. CSDST is a remnant tract arising superficially from the skin or subcutaneous plane, extending deep and terminating variably at the spinal cord, meninges or myofascial plane. A newborn’s neural system is usually preserved, with usual presentation being with skin stigmata. Nevertheless, this apparently benign sounding entity is associated with various other spinal dysraphisms and predispose the patient to multiple dreadful complications. Thus, a complete evaluation of a dorsal opening is cardinal and a conservative management is discouraged.